2018
DOI: 10.1214/17-aos1673
|View full text |Cite
|
Sign up to set email alerts
|

Extremal quantile treatment effects

Abstract: This paper establishes an asymptotic theory and inference method for quantile treatment effect estimators when the quantile index is close to or equal to zero. Such quantile treatment effects are of interest in many applications, such as the effect of maternal smoking on an infant's adverse birth outcomes. When the quantile index is close to zero, the sparsity of data jeopardizes conventional asymptotic theory and bootstrap inference. When the quantile index is zero, there are no existing inference methods dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 55 publications
0
33
0
1
Order By: Relevance
“…To be more specific, there exists γ>0 such that limtQε()1prefix−1tuQε()1prefix−1t=uγ for any u > 0. The real‐valued parameter γ is referred to as the extreme value index (de Haan & Ferreira, 2006; Gomes & Guillou, 2015; Zhang, 2018). It is important to note that Equation () implies that the conditional distribution of the response Y given Z and X also has a heavy right tail with the same extreme value index γ.…”
Section: Estimation Methodsmentioning
confidence: 99%
“…To be more specific, there exists γ>0 such that limtQε()1prefix−1tuQε()1prefix−1t=uγ for any u > 0. The real‐valued parameter γ is referred to as the extreme value index (de Haan & Ferreira, 2006; Gomes & Guillou, 2015; Zhang, 2018). It is important to note that Equation () implies that the conditional distribution of the response Y given Z and X also has a heavy right tail with the same extreme value index γ.…”
Section: Estimation Methodsmentioning
confidence: 99%
“…The propensity score Π(x) is generally unknown in practice and needs to be estimated. In this paper, we follow Hirano et al (2003), Firpo (2007) and Zhang (2018) to use the sieve method, a nonparametric regression method, for the estimation of the propensity score. Suppose that we observe n independent copies (Y i , D i , X i ) n i=1 of (Y, D, X).…”
Section: Propensity Score Estimationmentioning
confidence: 99%
“…The asymptotic results for fixed τ in Firpo (2007) no longer hold in this framework. Zhang (2018) established the asymptotic theory for the estimator proposed by Firpo (2007) with changing levels τ n . In particular, he distinguished between the intermediate τ n -QTE where nτ n → ∞ and the moderately extreme τ n -QTE where nτ n → d > 0; note that nτ n is the expected number of observations below the τ n -quantile in a sample of size n. In the intermediate case, he showed that the estimator is asymptotically normal and suggested a valid full-sample bootstrap confidence interval to quantify the uncertainty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They applied this approach to the estimation of the black wage gap for young males in the US. Zhang (2015) employed extremal quantile regression methods to estimate tail quantile treatment effects under a selection on observables assumption. Notation: The symbol → d denotes convergence in law.…”
Section: Introductionmentioning
confidence: 99%